Stability and adaptability of sweet orange using mixed models - Capistrano, Márcia da Costa; Andrade Neto, Romeu de Carvalho; dos Santos, Vanderley Borges; Lessa, Lauro Saraiva; Resende, Marcos Deon Vilela de; Gurgel, Fábio de Lima (Comunicata Scientiae, 2020)
Evaluations with sweet oranges are usually performed in several harvests and places to verify the differential behavior according to the environmental variations. This makes the selection by traditional statistical methodologies more and more difficult since they have limitations in the case of data unbalanced, common in citrus during the experimental phase due to the possibility of plot loss over the years. The objective of this work was to estimate the temporal stability and adaptability of sweet orange genotypes cultivated in eight crops under the edaphoclimatic conditions of Rio Branco, Acre. The experimental design used was in randomized blocks containing 55 genotypes and three replications. Four agronomic characteristics were evaluated during eight harvests. The genetic parameters were estimated using the REML/BLUP methodology. After detecting the presence of significant interaction between genotypes and environments, stability and adaptability analyzes were conducted by the methods of the harmonic mean of the genotypic values ​​(HMGV), the relative performance of the genetic values ​​(RPGV) and the harmonic mean of the relative performance of the genotypic values ​​(HMRPGV). The HMRPGV can be used to select stable, adapted and productive sweet orange genotypes. The number 48, 19, 5, 14, 2, 47 and 37 sweet orange genotypes can be selected for cultivation in an environment similar to the one studied, as they simultaneously present high stability, adaptability and productivity.